Atypical mismatch negativity to distressful voices associated with conduct disorder symptoms. (23rd May 2013) - Hung, An‐Yi; Ahveninen, Jyrki; Cheng, Yawei
<x xml:space="preserve">Abstract</x> Background Although a general consensus holds that emotional reactivity in youth with conduct disorder (CD) symptoms arises as one of the main causes of successive aggression, it remains to be determined whether automatic emotional processing is altered in this population. Methods We measured auditory event‐related potentials (ERP) in 20 young offenders and 20 controls, screened for DSM‐IV criteria of CD and evaluated using the youth version of Hare Psychopathy Checklist (PCL:YV), State‐Trait Anxiety Inventory (STAI) and Barrett Impulsiveness Scale (BIS‐11). In an oddball design, sadly or fearfully spoken 'deviant' syllables were randomly presented within a train of emotionally neutral 'standard' syllables. Results In young offenders meeting with CD criteria, the ERP component mismatch negativity (MMN), presumed to reflect preattentive auditory change detection, was significantly stronger for fearful than sad syllables. No MMN differences for fearful versus sad syllables were observed in controls. Analyses of nonvocal deviants, matched spectrally with the fearful and sad sounds, supported our interpretation that the MMN abnormalities in juvenile offenders were related to the emotional content of sounds, instead of purely acoustic factors. Further, in the young offenders with CD symptoms, strong MMN amplitudes to fearful syllables were associated with high impulsive tendencies (PCL:YV, Factor 2). Higher trait and state anxiety, assessed by STAI, were positively correlated with P3a amplitudes to fearful and sad syllables, respectively. The differences in group‐interaction MMN/P3a patterns to emotional syllables and nonvocal sounds could be speculated to suggest that there is a distinct processing route for preattentive processing of species‐specific emotional information in human auditory cortices. Conclusions Our results suggest that youths with CD symptoms may process distressful voices in an atypical fashion already at the preattentive level. This auditory processing abnormality correlated with increased impulsivity and anxiety. Our results may help to shed light on the neural mechanisms of aggression.